2007
DOI: 10.4103/0028-3886.37093
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life using QOLIE-31: Before and after epilepsy surgery a prospective study at a tertiary care center

Abstract: Complete seizure-free state after surgery is associated with very significant improvement in HRQOL parameters. Several, but not all parameters of HRQOL as assessed by QOLIE-31, improved after surgery even in the poor seizure outcome group. The improvement in domains of seizure worry, overall QOL, emotional wellbeing and social functioning is significantly more in those patients in whom complete seizure-free state is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…Earlier studies conducted on PWE in India using QOLIE-31 showed mean total QOL score ranging from 38.4 to 68. [ 19 20 21 22 23 ] In our study, mean total QOL score was 60.29 which was within the range of scores observed earlier and indicate good total QOL score. Various studies showed high and least scores in various subscales of QOLIE-31 such as highest in cognitive functioning and least score in energy fatigue;[ 19 ] highest in emotional well-being and least score in seizure worry;[ 20 ] highest in energy/fatigue and least score in overall QOL;[ 22 ] and highest in medication effects and least score in seizure worry.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Earlier studies conducted on PWE in India using QOLIE-31 showed mean total QOL score ranging from 38.4 to 68. [ 19 20 21 22 23 ] In our study, mean total QOL score was 60.29 which was within the range of scores observed earlier and indicate good total QOL score. Various studies showed high and least scores in various subscales of QOLIE-31 such as highest in cognitive functioning and least score in energy fatigue;[ 19 ] highest in emotional well-being and least score in seizure worry;[ 20 ] highest in energy/fatigue and least score in overall QOL;[ 22 ] and highest in medication effects and least score in seizure worry.…”
Section: Discussionsupporting
confidence: 87%
“…Greater the score, better the QOL. QOL in epilepsy-31 (QOLIE-31) questionnaire has been validated in Marathi-,[ 19 20 ] Malayalam-,[ 21 ] Hindi-,[ 22 23 ] and Kannada-[ 24 ] speaking populations of India. Cronbach's alpha and intraclass correlation coefficient obtained for QOLIE-31 in the present study were 0.946 and 0.974, respectively, which indicated good internal consistency and reproducibility of the instrument for assessment of QOL for the population of the present study.…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%
“…Only a single QOL domain correlated with absolute seizure frequency, overall QOL, but two domains including overall QOL and social function, along with overall score correlated with perceived change in seizure frequency. Like previous studies,6,7,13,14 in our study more QOL domains correlated with perceived change in frequency rather than absolute seizure frequency. Therefore, we speculate that QOL has determinants other than epilepsy-related variables, which we did not measure in this study.…”
Section: Discussionsupporting
confidence: 85%
“…[141821] Psychiatric outcome and neuropsychologic and psychosocial function after surgery usually improves, with worsening related predominantly to the persistence of seizures. Employment status and activities of daily living in general improve, mortality is decreased and medication regimens are reduced about 1 year after surgery gradually.…”
Section: Investigations For Epilepsy Surgerymentioning
confidence: 99%
“…Employment status and activities of daily living in general improve, mortality is decreased and medication regimens are reduced about 1 year after surgery gradually. [18] Stopping the drugs is to be done only in select cases as chance of recurrence is dependent on several factors. Hence the patient usually remains on a moderate dose of at least one drug 2-3 years after surgery, this decision should be taken only at a trained centre preferably by the epileptologist.…”
Section: Investigations For Epilepsy Surgerymentioning
confidence: 99%